Medium rare : exploring archives and their conversion from original to digital (part one : lessons from the history of print media) - Latham, Kiersten F. (2021)
This paper, which will be published in two parts, explores the physicality of archival materials in the context of the digital age. This first part reviews key lessons in the history of new technologies that have affected archival practice. The issues and problems we now face with conversion of physical archives to digital form are not entirely new. Throughout time, humans have gone through similar major transformations which affected not only culture and behavior but cognition in relation to information acquisition—the conversion from oral transmission to written or from locally available written media to mass-produced forms of communication are examples. This article provides a brief review of these historical processes and gives an overview of some of the lessons we can learn from them. Part Two (which will be published in the March 2011 issue of LIBRES) will explore a holistic understanding of paper-based knowledge transmission—specifically archives—in the context of the digital access movement.